Newly observed peroxides and the water effect on the formation and removal of hydroxyalkyl hydroperoxides in the ozonolysis of isoprene - D. Huang (Atmospheric Chemistry and Physics, 2013)
The ozonolysis of alkenes is considered to be an important source of atmospheric peroxides, which serve as oxidants, reservoirs of HOx radicals, and components of secondary organic aerosols (SOAs). Recent laboratory investigations of this reaction identified hydrogen peroxide (H2O2) and hydroxymethyl hydroperoxide (HMHP) in ozonolysis of isoprene. Although larger hydroxyalkyl hydroperoxides (HAHPs) were also expected, their presence is not currently supported by experimental evidence. In the present study, we investigated the formation of peroxides in the gas phase ozonolysis of isoprene at various relative humidities on a time scale of tens of seconds, using a quartz flow tube reactor coupled with the online detection of peroxides. We detected a variety of conventional peroxides, including H2O2, HMHP, methyl hydroperoxide, bis-hydroxymethyl hydroperoxide, and ethyl hydroperoxide, and interestingly found three unknown peroxides. The molar yields of the conventional peroxides fell within the range of values provided in the literature. The three unknown peroxides had a combined molar yield of ~ 30% at 5% relative humidity (RH), which was comparable with that of the conventional peroxides. Unlike H2O2 and HMHP, the molar yields of these three unknown peroxides were inversely related to the RH. On the basis of experimental kinetic and box model analysis, we tentatively assigned these unknown peroxides to C2−C4 HAHPs, which are produced by the reactions of different Criegee intermediates with water. Our study provides experimental evidence for the formation of large HAHPs in the ozonolysis of isoprene (one of the alkenes). These large HAHPs have a sufficiently long lifetime, estimated as tens of minutes, which allows them to become involved in atmospheric chemical processes, e.g., SOA formation and radical recycling.